PERLINDUNGAN KONSUMEN TERHADAP PENCEGAHAN KEJAHATAN PHISING DALAM PENGGUNAAN LAYANAN PERBANKAN DIGITAL - Dian Fitriana; Aliya Sandra Dewi; Errizka Fitriamadewi Bey (Collegium Studiosum Journal, 2026)
The development of digital banking services has provided convenience for the public in conducting financial transactions quickly and efficiently. However, these technological advancements have also increased the risk of cybercrime, one of which is phishing. Phishing is a form of fraud that aims to obtain customers’ personal data through social engineering by impersonating trusted institutions, including banks. This study aims to analyze the legal protection for digital banking consumers in preventing and addressing phishing crimes, as well as the mechanisms for restoring the rights of customers who suffer losses. The research method used in this study is normative legal research with statutory and conceptual approaches. The results indicate that legal protection for digital banking customers has been regulated in several laws and regulations, including Law Number 8 of 1999 concerning Consumer Protection, Law Number 27 of 2022 concerning Personal Data Protection, the Electronic Information and Transactions Law, and Financial Services Authority Regulation Number 6/POJK.07/2022 concerning Consumer and Public Protection in the Financial Services Sector. These protections are implemented through preventive measures such as strengthening security systems, educating the public, and supervising digital service providers. In addition, repressive measures are also available through complaint mechanisms, dispute resolution through non-litigation and litigation processes, and the provision of compensation or reimbursement to customers who experience losses due to phishing crimes.